Inovasi Pembelajaran : Penilaian Mahasiswa Berbasis Sistem Berdasarkan Perspektif Motivasi Belajar dan Pengaruh Penggunaan Sistem - Andhika Herayono; Dedy Irfan; Resmi Darni; Rizky Ema Wulansari; Elfi Tasrif; Qothrun Nada Ma'ruf Batubara (Journal for Lesson and Learning Studies, 2023)
The assessment process carried out by lecturers for students still uses previous utilization procedures, such as processing grades with Microsoft Excel, so it is less effective. This research aims to analyze system-based student assessments based on the perspective of learning motivation and the influence of system use. This type of research is quantitative research. The total research population is 100 students. The research sample was 55 students using random sampling techniques. The data collection method uses a questionnaire. The data collection instrument is a questionnaire sheet. The technique used to analyze the data is inferential statistics with Pearson correlation calculations used to analyze the relationship between the two variables. The analysis results show a strong positive correlation between learning motivation and the effect of using the assessment system. The correlation value is close to perfect, indicating that the higher the student's learning motivation, the greater the positive effect of using the assessment system on learning outcomes. These significant results emphasize the importance of a transparent assessment system in increasing student learning motivation. Students who clearly understand how assessments are carried out and how grades are assigned tend to be more motivated to achieve higher academic achievements. The contribution of this research is that innovation in the development and improvement of technology-based assessment systems is very relevant in supporting the achievement of better learning outcomes.